Intervention to Improve Diarrhea-Related Knowledge and Practices Among Informal Healthcare Providers in Slums of Kolkata. (27th October 2021) - Mahapatra, Tanmay; Mahapatra, Sanchita; Datta Chakraborty, Nandini; Raj, Aparna; Bakshi, Bhawani; Banerjee, Barnali; Saha, Snehasish; Guha, Abhijit; Dutta, Shanta; Kanungo, Suman
Abstract: Background: In the densely populated slums of Kolkata, informal healthcare providers' (IHP) diarrhea-related knowledge and rationality of practices should be improved to reduce risk of adverse outcome, expenditure, and antimicrobial resistance. Methods: A multicomponent intervention was conducted among 140 representative IHPs in the slums of 8 wards in Kolkata to assess its impact on their diarrhea-related knowledge and practice. Six intervention modules in local languages were provided (1 per month) with baseline (N = 140) and postintervention (N = 124) evaluation. Results: Mean overall (61.1 to 69.3; P < .0001) and domain-specific knowledge scores for etiology/spread (5.4 to 8.1; P < .0001), management (6.4 to 7.2; P < .0001), and oral rehydration solution ([ORS] 5.7 to 6.5; P < .0001) increased significantly (at α = 0.05) after intervention and were well retained. Impact on knowledge regarding etiology/spread (adjusted odds ratio [aOR] = 5.6; P < .0001), cholera (aOR = 2.0; P = .0041), management (aOR = 3.1; P < .0001), ORS (aOR = 2.3; P = .0008), and overall (aOR = 4.3; P < .0001) were significant. Intervention worked better for IHPs who practiced for ≥10 years (aOR = 3.2; P < .0001), untrained IHPs (aOR = 4.8; P < .0001), and pharmacists (aOR = 8.3; P < .0001). Irrational practices like empirical antibiotic use for every cholera case (aOR = 0.3; P < .0001) and investigation for every diarrhea case (aOR = 0.4; P = .0003) were reduced. Rationality of testing (aOR = 4.2; P < .0001) and antibiotic use (aOR = 1.8; P = .0487) improved. Conclusions: Multicomponent educational intervention resulted in sustainable improvement in diarrhea-related knowledge and practices among IHPs in slums of Kolkata. Policy implications should be advocated along with implementation and scale-up.